2016
DOI: 10.1016/j.appet.2016.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Power of Food Scale in association with weight outcomes and dieting in a nationally representative cohort of U.S. young adults

Abstract: Food reward sensitivity may influence susceptibility to overeating in a permissive food environment, contributing to unintended weight gain and intentional weight loss behavior. This study examined associations of food reward sensitivity, assessed by the Power of Food Scale (PFS), with weight outcomes and dieting in a nationally representative cohort of U.S. emerging adults. Wave 5 (W5, 5th year of follow-up) respondents from the NEXT Generation Health Study were included (N=2202, W5 age=20.3±0.02 years). Base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
4
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 58 publications
1
12
4
2
Order By: Relevance
“…Interestingly, the AN and ARFID groups showed distinct response patterns on the PFS. AN and ARFID groups scored similarly on the Food Tasted and Food Present subscales but lower than published means in a community sample of adults (Lipsky et al, 2016), indicating that neither clinical group reported high levels of pleasure in eating or difficulty in resisting eating palatable foods. However, individuals with AN scored higher than those with ARFID on the Food Available subscale, suggesting that those with AN report higher urges to eat and thoughts about food when food is not present than those with ARFID.…”
Section: Discussioncontrasting
confidence: 65%
“…Interestingly, the AN and ARFID groups showed distinct response patterns on the PFS. AN and ARFID groups scored similarly on the Food Tasted and Food Present subscales but lower than published means in a community sample of adults (Lipsky et al, 2016), indicating that neither clinical group reported high levels of pleasure in eating or difficulty in resisting eating palatable foods. However, individuals with AN scored higher than those with ARFID on the Food Available subscale, suggesting that those with AN report higher urges to eat and thoughts about food when food is not present than those with ARFID.…”
Section: Discussioncontrasting
confidence: 65%
“…Psychological factors may affect weight loss indirectly by influencing weight loss‐related behaviours . To date, only one previous study has investigated the relation between power of food and weight loss in a non‐clinical sample . In contrast to our findings, no association was found .…”
Section: Discussioncontrasting
confidence: 99%
“…To date, only one previous study has investigated the relation between power of food and weight loss in a non‐clinical sample . In contrast to our findings, no association was found . However, power of food is associated with dieting behaviour and greater risk of perceived overweight .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Individuals who exhibit high scores in uncontrolled eating at baseline generally tend to gain weight over time (French et al, 2012; Figure 2A, line 4). Longitudinal studies have observed this trend using questionnaires reflecting (i) emotional eating (Van Strien et al, 2013;Boggiano et al, 2015), (ii) binge eating (Quick et al, 2013;Micali et al, 2014), (iii) disinhibited eating (Hays et al, 2002;Chaput et al, 2010Chaput et al, , 2011, (iv) feelings of hunger (Hays et al, 2006) and (v) food reward sensitivity (Lipsky et al, 2016). Additionally, scores in uncontrolled eating seem to predict weight outcomes in clinical populations undergoing weight loss treatments.…”
Section: Longitudinal Associations Between Uncontrolled Eating and Bomentioning
confidence: 98%